Acoustic Strength Comparison between Green Turtle and Fish Using Echo Sounder - Sunardi, S.; Mahfurdz, A.; Hamzah, Ahmad (2014)
Acoustic power measurement using dual frequency echo sounder operated 200 kHz were conducted on Green Turtle and fish. The echo signal from Sensitivity Time Control (STC) output was digitized at a sampling rate 1MHz using multifunction DAQ device (Measurement Computing USB1208HS). The animal's position in the water was set in horizontal position toward to the transducer and the measurement was conducted at different orientation of the animals. The data was analyzed in both frequency and time domain. The transmit pulse of the signal has been remove first to ensure it's not affect the result. The finding demonstrated, there are significant different echo strength between Green Turtle and fish. The shell and plastron is the part that gives the highest value for both turtles, meanwhile lateral side contributed high echo compared to other side of fish. Through analysis, positive progress has been made toward the understanding of the unique scattering by sea turtle and fish. These findings are considered important in enriching the acoustic detection, especially to determine the best method to distinguish sea turtle and fish.